Soft plastron, soft carapace with skeletal abnormality in juvenile tortoises - Heuser, W.; Pendl, H.; Knowles, N. J.; Keil, G.; Herbst, W.; Lierz, M.; Kaleta, E. F. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2014)
Objective: A disease is described in juvenile tortoises (Testudo graeca and Geochelone elegans) consisting mainly of a soft carapace, soft plastron and deformed skeleton. The aim of this study was to determine histopathological lesions and the biological properties of the isolated viruses. Materials and methods: Clinical signs and gross pathology were determined on diseased and healthy appearing tortoises. Paraffin sections were stained with HE, PAS and Prussian Blue and histologically examined. Terrapene heart (TH-1) cell cultures served for virus isolations from 64 tissues and 104 swabs. One isolate (isolate 1243/37 tongue) was used in neutralization tests on 19 sera. Results: Retarded growth and increasingly soft plastron and carapace were the prominent signs in diseased tortoises. Pathological lesions consisted of dilated urinary sac, enlarged kidneys and livers. Histopathologically, hepatic hemosiderosis, hypoplastic anaemia, congestive glomerulonephrosis and osteodystrophy were seen. A novel virus (“virus X”) was isolated from 64 organs and 79 of 104 swabs. The isolated viruses were identified as a novel chelonid picornavirus based on cytopathic effect, resistance to chloroform and stability at low pH. Co-cultivation with 5-iodo-2’-deoxyuridine and actinomycin D did not reduce virus titres. Electron microscopically, round, non-enveloped particles (25–30 nm) were detected. Neutralizing antibodies to the isolate 1243/37tongue were present in 17 of 19 sera from seven species of tortoises. Conclusion and clinical relevance: Nephropathy, osteodystrophy and virus isolations suggest a viral aetiology. Metabolic bone disease is the major differential diagnosis. Further investigations in vivo are needed to evaluate the likely effects of the picornavirus on tortoises.
Keywords: Virus infection; nephropathy; osteodystrophy